Service Quality of Population Administration at the Department of Population and Civil Registration of Mojokerto City - Farell Ramses Christfiant; Meirinawati M; Eva Hany Fanida; Fitrotun Nizwah (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Department of Population and Civil Registration of Mojokerto City has introduced a website-based service innovation, â€œPak Mo,â€ as an effort to improve the effectiveness, efficiency, and accessibility of population administration services. However, in its implementation, various technical and non-technical obstacles are still encountered, which may potentially affect the overall quality of service delivery. This study aims to describe the quality of population administration services provided by Dispendukcapil of Mojokerto City at MPP Gajah Mada. This study uses a qualitative approach with data collection techniques through observation, interviews, and documentation. Research informants consist of Dispendukcapil officials, service officers, and community members who use population administration services. The implementation of population administration services still faces several obstacles, such as limited public understanding regarding administrative requirements, incomplete community documents, and limited supporting service facilities at certain times. Service quality analysis uses five service quality dimensions, namely tangible, reliability, responsiveness, assurance, and empathy. The results show that in the tangible and reliability dimensions, Dispendukcapil services at MPP Gajah Mada have been running well through the availability of service facilities and the implementation of clear standard operating procedures. However, in the responsiveness dimension, there are still obstacles related to response time to several community problems. In the assurance dimension, services have been able to provide data security guarantees and service certainty to the community. Meanwhile, in the empathy dimension, officers have shown friendliness and have tried to understand community needs in the service process.